PrestaShop module development : develop and customize powerful modules for PrestaShop 1.5 and 1.6 - Serny, Fabien (Community experience distilled., 2014)
If you are a developer who is new to PrestaShop and wants to get a good foundation in development on the PrestaShop framework, this book is for you. It's assumed that you will have some experience with PHP5, jQuery, and HTML/CSS (no need to be an expert on it).